The InfluencePengaruh Penggunaan Media Google Classroom Pada Proses Pembelajaran Sejarah Terhadap Keaktifan Siswa Kelas XI IPS SMA Negeri 1 Cilegon - Nada Adilah; Arif Permana Putra; Agus Rustamana (LPPM Institut Nasional Laa Roiba Bogor, 2022)
This study aims to determine the effect of using media google classroom on the history learning process on the activeness of students in class XI IPS SMA Negeri 1 Cilegon. This research is an associative research using a quantitative approach. The population used in this study were 135 students of class XI Social Sciences SMA Negeri 1 Cilegon, using a sample of 57 students. Methods of data collection using interviews, questionnaires and documentation. With descriptive and inferential analysis techniques. The results of this study indicate that: there is a positive and significant effect of using media google classroom on the history learning process on the activeness of students in class XI IPS SMA Negeri 1 Cilegon. Based on the comparison between tarithmetic = 9.407 ttable = 1.673, then H1 is accepted and H0 is rejected. From the results of the simple regression equation, the regression correlation coefficient, which is 0.617, is obtained from the value of R square which shows that the coefficient value of 61.7% is positive, this explains that the use of media google classroom has a significant positive effect on student activity where the first meeting amounted to 68% increased at the second meeting 77% and very significant at the third meeting by 95%. It can be concluded that there is an effect of using google classroom on student activity in learning history of students in class XI IPS SMA Negeri 1 Cilegon. The activeness of students in the history learning process can be seen from the delivery of opinions verbally, listening, and writing the learning media google classroom. Keywords: Google Classroom, History Learning, Student Activity.